Security Strategies and The Management of Armed Conflict in Benue State - Dominic Aondona Iornumbe; Liman Abdullahi Nuhu; Andrew Zamani (Jurnal Restorasi : Hukum dan Politik, 2025)
Armed conflicts happen to be one of the major challenges that have threatened the security and unity of the North-Central Nigeria especially in Benue State. The state has been rocked by attacks emaciating from the conflict, which has been seen as a new wave of violence which primarily stems from disputes over grazing areas for cattle. The necessity to provide food of crops and animal origin, as well as raw materials for industry and export in order to meet ever-growing demands, has led to extensive use of land. The conflict has demonstrated high potential to exacerbate the insecurity and food crisis particularly in rural communities where most of the conflicts are localized, with reverberating repercussions nationwide. As a result, this paper examined the use of dialogue and infrastructural development to resolve the farmers/herders’ conflict in Benue State from 2008 – 2024. The paper adopted the Frustration Aggression Theory to ascertain and justify the reasons for the conflict. A simple proportional percentage was used to distribute the total questionnaires for each of the local governments where 399 respondents were targeted to participate in the research but data were collected from 386 respondents. Findings from the research reveals that the land is a pivotal point in the conflict as the farmers use the land for cultivation, the herders equally use it for grazing. It was also discovered that the leaders rejected the concept of separating the farming area from the grazing area, an idea which could have reduced direct collision between farmers and herders. The paper thus recommended that the government should be more proactive in the enactment of appropriate policies, dialogue and infrastructural development for resolving herders and farmer’s conflict in Benue State.